Quill mites (Acari: Syringophilidae) of the Palaearctic region - Skoracki, Maciej (Zootaxa, 2011)
The fauna of quill mites of the family Syringophilidae (Acari: Prostigmata: Cheyletoidea) of the Palaearctic Region is comprehensively revised. The external morphology of adults and immature instars was studied in detail. All known 118 species grouped in 32 genera and 2 subfamilies occuring in the Palaearctic Region are examined and keyed. Critical reviews of host associations, occupying habitat, and distribution are given for all mite species. Six new genera are proposed, 4 in the subfamily Syringophilinae: Betasyringophiloidus gen. nov., Krantziaulonastus gen. nov., Paraniglarobia gen. nov., Pteroclidisyringophilus gen. nov.; and 2 in the subfamily Picobiinae: Neopicobia gen. nov., and Rafapicobia gen. nov. Twenty five new species are described in the subfamily Syringophilinae: Aulobia leucostictus sp. nov., Aulonastus lanius sp. nov., A. loxius sp. nov., A. anthus sp. nov., A. fringillus sp. nov., Betasyringophiloidus saxicolus sp. nov., B. phoenicurus sp. nov., Krantziaulonastus oryzivorus sp. nov., K. lonchurus sp. nov., Meitingsunes columbicus sp. nov., Neoaulonastus remizus sp. nov., N. caligatus sp. nov., N. aegithalos sp. nov., N. picidus sp. nov., N. riparius sp. nov., Selenonycha chradriiformicus sp. nov., Syringophiloidus philomelosus sp. nov., S. petronicus sp. nov., S. parapresentalis sp. nov., S. coccothraustes sp. nov., Syringophilopsis idunae sp. nov., S. muscicapus sp. nov., S. passericus sp. nov., S. nucifragus sp. nov., Torotrogla pycnonotus sp. nov. and five new species are described in the subfamily Picobiinae: Picobia cetti sp. nov., P. riparius sp. nov., P. eremophila sp. nov., P. galerida sp. nov., and Rafapicobia zirnitra sp. nov. The following new combinations are proposed: Aulobia stachyris (Bochkov et al., 2000) comb. nov., Betasyringophiloidus motacillae (Bochkov and Mironov, 1998) comb. nov., B. schoeniclus (Skoracki, 2002) comb. nov., Columbiphilus alectoris (Fain et al., 2000) comb. nov., Columbiphilus polonica (Skoracki et al., 2001) comb. nov., C. pteroclesi (Skoracki and OConnor, 2010) comb. nov., Cuculisyringophilus chirovi (Bochkov and Mironov, 1998) comb. nov., Krantziaulonastus buczekae (Skoracki, 2002) comb. nov., Krantziaulonastus galbulicus (Skoracki, 2008) comb. nov., Neoaulonastus bisetatus (Fritsch, 1958) comb. nov., Neopicobia anthi (Fritsch, 1958) comb. nov., Neopicobia cardinalis (Skoracki et al., 2010) comb. nov., N. carpodacus (Skoracki et al., 2010) comb. nov., N. epthianura (Skoracki et al., 2008) comb. nov., N. glossopsitta (Skoracki et al., 2008) comb. nov., N. locustella (Skoracki et al., 2004) comb. nov., N. modularis (Skoracki and Magowski, 2001) comb. nov., N. pyrrholaemus (Skoracki and Glowska, 2008) comb. nov., N. troglodytes (Skoracki et al., 2010) comb. nov., N. zumpti (Lawrence, 1959) comb. nov., Paraniglarobia calidridis (Bochkov and Mironov, 1998) comb. nov., Paraniglarobia skorackii (Bochkov and Galloway, 2004) comb. nov., Pteroclidisyringophilus re (Skoracki and OConnor, 2010) comb. nov. Three species are considered as incertae sedis: Picobia brotogeris Fain et al., 2000, P. leucophaeus Skoracki et al., 2010, P. poicephali Skoracki and Dabert, 2002. Keys to the syringophilid genera and all Palaearctic species are provided. Main aspects of host–parasite relationships are discussed.